1994
DOI: 10.1136/hrt.71.5.431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta blockade on the neurohumoral and cardiopulmonary response to dynamic exercise in cardiac transplant recipients.

Abstract: Objective-To determine the effects of a small dose of ft blocker on neurohumoral and cardiopulmonary responses after cardiac transplantation. Background-Cardiac transplant recipients have a reduced exercise capacity and abnormal cardiovascular responses to exercise. The sympathoadrenal response to exercise has been shown to be abnormal with high venous noradrenaline. The effect of ft blockade on these neurohumoral mechanisms has not been defined. Methods-10 non-rejecting cardiac transplant recipients were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…Recent multicenter, prospective, randomised and controlled trials have demonstrated a significant reduction in myocardial infarction, death from heart failure and decrease of hospitalisation rate in patients treated with ivabradine [11][12][13]. Ivabradine treatment was not associated with deterioration of blood pressure, cardiac conduction, myocardial contractility or peripheral vascular tone, thereby distinguishing it from beta blocker or calcium channel blockers [4,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent multicenter, prospective, randomised and controlled trials have demonstrated a significant reduction in myocardial infarction, death from heart failure and decrease of hospitalisation rate in patients treated with ivabradine [11][12][13]. Ivabradine treatment was not associated with deterioration of blood pressure, cardiac conduction, myocardial contractility or peripheral vascular tone, thereby distinguishing it from beta blocker or calcium channel blockers [4,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 A few authors have blockers in patients with heart disease, 5 hypertendescribed increased plasma ANP or ANP/ sion, 6 renal replacement therapy 7 and cardiac transpulmonary capillary wedge pressure ratios after plantation. 8 An explanation for the presence or ACE inhibition, both in hypertensive subjects and absence of a stimulatory effect of beta-blockers on cardiac patients. 20,21 In those studies in which mean plasma ANP is not readily apparent; both effects ANP levels are unmodified by ACE inhibitors, the have been reported with the same drug, 2,8 with variance of ANP is usually very large, reflecting agents sharing the same pattern of cardioselectivresponses of opposite direction (ie, increases and ity, 3,7 and in the same disease state.…”
Section: Introductionmentioning
confidence: 99%
“…8 An explanation for the presence or ACE inhibition, both in hypertensive subjects and absence of a stimulatory effect of beta-blockers on cardiac patients. 20,21 In those studies in which mean plasma ANP is not readily apparent; both effects ANP levels are unmodified by ACE inhibitors, the have been reported with the same drug, 2,8 with variance of ANP is usually very large, reflecting agents sharing the same pattern of cardioselectivresponses of opposite direction (ie, increases and ity, 3,7 and in the same disease state. 3,6 Post-exercise decreases) among the subjects studied.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being recommended for rate control by ISHLT, ÎČ‐blockers effect on post‐HTx exercise capacity is controversial. Although a recent study did not find harmful results, earlier data have raised concerns against the therapeutic use of ÎČ‐blockers in HTx recipients and showed that acute ÎČ‐blockade, especially if not selective, negatively affects cardiac performance and reduces exercise capacity after HTx secondary to abnormal sympathoadrenal response . This detrimental effect of ÎČ‐blockade on exercise capacity was more pronounced in patients with re‐innervated than deinnervated transplanted hearts .…”
Section: Discussionmentioning
confidence: 96%
“…Nondihydropyridine calcium channel blockers and ÎČ‐blockers have been recommended for rate control by the International Society of Heart and Lung transplantation (ISHLT) . Previous data revealed that ÎČ‐blockers should be used with caution in cardiac transplant recipients due to their negative effect on ventricular performance, as well as on exercise tolerance and on cardiovascular response to exercise …”
Section: Introductionmentioning
confidence: 99%